Pemaknaan Semiotika pada Poster dalam Kampanye Capres dan Cawapres Tahun 2024: Tinjauan Semantik - najmatuzzahiroh; nova riyanti; anis rahmadhani; yuentie sova puspidalia (Hasta Wiyata, 2025)
This research was promoted by several posters in the 2024 capres and cawapres campaigns namely the couple Anies – Baswedan, Prabowo Subianto – Gibran Rakabuming Raka and Ganjar Pranowo – Mahfud M.D. The research aims to analyze semiotic digestion on posters used in the presidential and vice presidential campaigns in the context of the General Election 2024, with a focus on semantic aspects. In a political context, posters are a powerful visual communication medium to convey a message to potential voters. In semiotic studies, posters can be studied from the point of view of symbols, icons, and indices that make up meaning. The research method used was a qualitative analysis of the campaign posters of various capres and cawapres candidates competing in the 2024 General Election. And also using content analysis techniques. Data is analyzed by considering semiotic elements such as images, text, colors, and layouts. The results show that semiotic fertilization on the 2024 capres and cawapres campaign posters was heavily influenced by the political, cultural, and social context at the time. Through semantic analysis, posters can reveal the values, visions, and missions of candidates, as well as try to influence voter perceptions and attitudes. For example, the use of certain colors, symbols, and specific visual language can arouse emotions, identification, and solidarity with a particular candidate.